2022
DOI: 10.1017/wet.2022.16
|View full text |Cite
|
Sign up to set email alerts
|

Seedbank management through an integration of harvest-time and postharvest tactics for Italian ryegrass (Lolium perenne ssp. multiflorum) in wheat

Abstract: Italian ryegrass is a major weed in winter cereals in the south-central United States (US). Harvest weed seed control (HWSC) tactics that aim to remove weed seed from crop fields are a potential avenue to reduce Italian ryegrass seedbank inputs. To this effect, a four-year, large-plot field study was conducted in College Station, Texas and Newport, Arkansas from 2016 to 2019. The treatments were arranged in a split-plot design. The main-plot treatments were: (1) no narrow-windrow burning (a HWSC strategy) + di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Variability in both studies is attributed to differences in initial seedbank densities and Italian ryegrass seed retention and production at harvest. Maity et al (2022) found that using NWB each year for 4 yr reduced Italian ryegrass soil seedbank size by 78% in Texas, while improving wheat yield. Compared to conventional harvest, NWB reduced Italian ryegrass plant populations during the growing season by 73%, 83%, and 88% in Texas; and by 8%, 55%, and 89% in Arkansas after the second, third, and fourth year of NWB, respectively.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Variability in both studies is attributed to differences in initial seedbank densities and Italian ryegrass seed retention and production at harvest. Maity et al (2022) found that using NWB each year for 4 yr reduced Italian ryegrass soil seedbank size by 78% in Texas, while improving wheat yield. Compared to conventional harvest, NWB reduced Italian ryegrass plant populations during the growing season by 73%, 83%, and 88% in Texas; and by 8%, 55%, and 89% in Arkansas after the second, third, and fourth year of NWB, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Compared to conventional harvest, NWB reduced Italian ryegrass plant populations during the growing season by 73%, 83%, and 88% in Texas; and by 8%, 55%, and 89% in Arkansas after the second, third, and fourth year of NWB, respectively. In combination with various herbicide treatments, their integrated management program led to large reductions in Italian ryegrass seed survival and annual fecundity (Maity et al 2022). Problematic status and a lack of regionally specific data in NWB systems makes Italian ryegrass an important candidate for this study.…”
Section: Introductionmentioning
confidence: 99%
“…crus-galli (barnyard grass) is one of the most noxious weeds in modern agriculture, and it affects relevant crops like rice, is dispersed worldwide, and has a tendency to grow in harsh climates; , and L. perenne (ryegrass), the major weed that affects wheat production worldwide …”
Section: Introductionmentioning
confidence: 99%